Children's Oncology Group's 2013 blueprint for research: Stem cell transplantation. Issue 6 (19th December 2012) - Grupp, Stephan A.; Dvorak, Christopher C.; Nieder, Michael L.; Levine, John E.; Wall, Donna A.; Langholz, Bryan; Pulsipher, Michael A.
Abstract The role of SCT in pediatric oncology has continued to evolve with the introduction of new therapeutic agents and immunological insights into cancer. COG has focused its efforts on the study of hematopoietic stem cell transplantation in the treatment of pediatric malignancies in several major multi‐institutional Phase II and Phase III studies. These studies include addressing the impact of allogenicity in ALL (ASCT0431), and establishing autologous stem cell transplant as the standard of care in neuroblastoma. Reducing transplant‐associated toxicity was addressed in the ASCT0521 study, where the TNFα inhibitor etanercept was tested for the treatment of idiopathic pneumonia syndrome. Impact of cell dose was explored in the single versus tandem umbilical cord blood study CTN‐0501, in close collaboration with the BMT‐CTN. Pediatr Blood Cancer 2013; 60: 1044–1047. © 2012 Wiley Periodicals, Inc.